2018
DOI: 10.5582/ddt.2018.01048
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a gnotobiotic silkworm model

Abstract: Gnotobiotic animals are useful for investigation of the effects of specific lactic acid bacteria on individual animals. Here we report that lactic acid bacteria colonize and proliferate in the intestinal tract of germ-free silkworms. When silkworms hatching from formalin-treated eggs were reared to fifth-instar larvae with an artificial diet containing antibiotics, bacteria and fungi were not observed in their intestines. An antibiotic-free diet supplemented with viable lactic acid bacteria, such as Enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Since the completion of the genome sequence, the silkworm ( Bombyx mori ) has become a widely used model insect for lepidopteran research, and a general model organism for life sciences, toxicology, and fungal infections ( International Silkworm Genome, 2008 ; Suetsugu et al, 2013 ; Meng et al, 2017 ; Abdelli et al, 2018 ; Nakajima et al, 2018 ; Matsumoto and Sekimizu, 2019 ). In previous research, we have demonstrated that the Bombyx mori ERR (BmERR) is involved in the growth and development of silkworm embryos and larvae by regulating the expression of glucose metabolism-related genes ( Long et al, 2020 ; Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the completion of the genome sequence, the silkworm ( Bombyx mori ) has become a widely used model insect for lepidopteran research, and a general model organism for life sciences, toxicology, and fungal infections ( International Silkworm Genome, 2008 ; Suetsugu et al, 2013 ; Meng et al, 2017 ; Abdelli et al, 2018 ; Nakajima et al, 2018 ; Matsumoto and Sekimizu, 2019 ). In previous research, we have demonstrated that the Bombyx mori ERR (BmERR) is involved in the growth and development of silkworm embryos and larvae by regulating the expression of glucose metabolism-related genes ( Long et al, 2020 ; Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%